At all costs - Gilstrap, John (New York : Warner Books, 1998)
A married couple on the FBI's most wanted list for 13 years sets out to learn who framed them. Jake and Carolyn Donovan were the sole survivors of an explosion in a munitions plant that killed 16 people and the FBI calls them terrorists.
National College of Business and Arts
Keywords: Fugitives from justice -- Fiction; Suspense fiction